Improved oral bioavailability of repaglinide, a typical BCS Class II drug, with a chitosan‐coated nanoemulsion. Issue 3 (12th June 2019) - Karami, Zahra; Saghatchi Zanjani, Mohammad Reza; Nasihatsheno, Nadia; Hamidi, Mehrdad
Abstract: The aim of the present study was to develop modified nanoemulsions to improve the oral bioavailability and pharmacokinetics of a poor water‐soluble drug, repaglinide (RPG). The repaglinide‐loaded nanoemulsions (RPG‐NEs) were prepared from olive oil as internal phase, span 80, tween 80, and poloxamer 188 as emulsifiers, using homogenization technique. The mean droplet size, zeta potential, and entrapment efficiency of RPG‐NEs were 86.5 ± 3.4 nm, −33.8 ± 2.1 mV, and 96.3 ± 2.3%, respectively. The chitosan‐coated RPG‐NEs (Cs‐RPG‐NEs) showed an average droplet size of 149.3 ± 3.9 nm and a positive zeta‐potential of +31.5 ± 2.8 mV. Drug release profile of RPG‐NEs was significantly higher than free drug in the simulated gastrointestinal fluids ( p < .005). The in vivo study revealed 3.51‐ and 1.78‐fold increase in the AUC0‐12h and C max of the drug, respectively, in RPG‐NEs‐receiving animals in comparison to the free drug. The pharmacokinetic analysis confirmed that Cs‐RPG‐NEs were more efficient than uncoated ones for the oral delivery of RPG. Cs‐RPG‐NEs showed a longer t 1/2 and higher AUC0‐∞ compared to control group. The relative bioavailability of Cs‐RPG‐NEs was higher than that of uncoated RPG‐NEs and free drug. Collectively, these findings suggest that chitosan‐coated nanoemulsions are promising carrier for improving the oral bioavailability of RPG. Abstract :